2018
DOI: 10.1021/acssuschemeng.8b04451
|View full text |Cite
|
Sign up to set email alerts
|

Lignosulfonate/Dicationic Ionic Liquid Composite as a Task-Specific Catalyst Support for Enabling Efficient Synthesis of Unsymmetrical 1,3-Diynes with A Low Substrate Ratio

Abstract: In Glaser heterocoupling reactions, one of the alkyne precursors have to be used in five to ten times of excess. This not only wasted the organic substrate, but also decreased the catalytic efficiency of the metal catalysts. To solve this problem, we prepared a lignosulfonate/dicationic ionic liquid composite via ion exchange process. The thereby obtained materials can be used as catalyst supports for preparing heterogeneous Cu-based catalysts. The supports and the catalysts were characterized by many physicoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 73 publications
(86 reference statements)
0
14
0
1
Order By: Relevance
“…In fact, starting from an alkynol and phenylacetylene, one of the alkyne precursors needs to be in excess to avoid a homocoupling reaction and to obtain a high yield of the heterocoupling product. For all these reasons, Lai et al developed a new catalyst consisting of lignosulfonate/DIL composite as a support for preparing a heterogeneous Cu-based catalyst (DIL@LS-TMEDA-Cu) [ 46 ]. Their strategy was to prepare a hydrogen-bond-active solid supporting material to allow a locally high concentration of the alkynol, in order to use a low substrate ratio of reactants, but at the same time, being a phenylacetylene a lipophilic molecule, the support should not be too hydrophilic.…”
Section: Applications In Organocatalysismentioning
confidence: 99%
“…In fact, starting from an alkynol and phenylacetylene, one of the alkyne precursors needs to be in excess to avoid a homocoupling reaction and to obtain a high yield of the heterocoupling product. For all these reasons, Lai et al developed a new catalyst consisting of lignosulfonate/DIL composite as a support for preparing a heterogeneous Cu-based catalyst (DIL@LS-TMEDA-Cu) [ 46 ]. Their strategy was to prepare a hydrogen-bond-active solid supporting material to allow a locally high concentration of the alkynol, in order to use a low substrate ratio of reactants, but at the same time, being a phenylacetylene a lipophilic molecule, the support should not be too hydrophilic.…”
Section: Applications In Organocatalysismentioning
confidence: 99%
“…One solution is to functionalize lignin with ILs to promote better compatibility between lignin and cellulose during fabrication. Recently Gu and Bai et al have shown that modification of the polyelectrolyte sodium lignosulfonate (SLS) with organic cations is feasible by cation exchange reactions, [26] and is a simple approach that does not require utilization of the OH functionality. Ion-exchange serves as a means to introduce functionality onto polyelectrolytes [27] and often changes its electrical, [28] chemical, [29] and thermal properties.…”
Section: Ligninisthesecondmostavailablebiopolymeronearthwithmentioning
confidence: 99%
“…However, the stability and durability of LS was very limited especially in polar solvents such as H 2 O, EtOH and at harsh conditions. In a further study of our previous work [ 15 ], a LS/dicationic ionic liquid composite was prepared via an ion exchange process, and then used as catalyst support for preparing a heterogeneous Cu-based catalyst, the thereby obtained catalyst displayed remarkable performance in the Glaser hetero-coupling reaction. Combining two successful attempts, a further study concerning improvement of the robustness of catalysts and active sites when using LS as support is urgently needed.…”
Section: Introductionmentioning
confidence: 99%